Pneumolysin Is a Key Factor in Misidentification of Macrolide-Resistant Streptococcus pneumoniae and Is a Putative Virulence Factor of S. mitis and Other Streptococci - Neeleman, Chris (American Society for Microbiology, 2004)
We evaluated the applicability of ply PCR for confirmation of the identification of Streptococcus pneumoniae. lytA PCR, 16S rRNA sequencing, and amplified-fragment length polymorphism were used as reference methods. In contrast to the lytA gene, the ply gene proved to be not specific for S. pneumoniae. The presence of the ply gene in other streptococci, in particular Streptococcus mitis, suggests that pneumolysin plays a pathogenic role.